Bilateral Asymmetrical Hip Dislocation in a 70-year-old Female: A Rare Case Report - T. V. Suresh; D. Naveen; K. Harish; Ravi M. Daddimani (Journal of Orthopedics, Traumatology and Rehabilitation)
Traumatic dislocation of the hip joint is a rare injury representing 2%–5% of all dislocations while bilateral hip dislocation accounts for 1.25% of all hip dislocations. Asymmetrical hip dislocations are even rarer accounting for approximately 0.01%–0.02% of all hip joint dislocations. We are reporting a case of bilateral asymmetrical hip dislocations with left-sided posterior dislocation and right anterior dislocation in a 70-year-old female following a road traffic accident. It is pertinent to thoroughly evaluate the patient on the Advanced Trauma Life Support guidelines. After evaluation, it is vital to reduce hip dislocation within 6 h from the time of injury to prevent complications like avascular necrosis of the femoral head. Relevant anatomy, injury mechanism, classification, diagnosis, associated injuries, treatment, and complications have also been discussed.